Binder, preparation method thereof, battery and electric equipment
By introducing acrylate polymers containing fluorine, cyano groups and crosslinkable segments into the positive electrode binder of lithium-ion batteries, the degradation and crosslinking problem of PVDF in a highly alkaline environment is solved, the rate performance and oxidation potential of the battery are improved, and the swelling and cost of the electrolyte are reduced.
Patent Information
- Application Number
- CN202311428036.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-28
- Publication Date
- 2025-04-29
AI Technical Summary
The positive electrode binder PVDF of existing lithium-ion batteries is prone to degradation and cross-linking in a highly alkaline environment, resulting in gelation of the positive electrode slurry and affecting processing performance. At the same time, alternative solutions such as polyimide-based binders and polyacrylonitrile copolymers have problems such as poor rate performance, high cost and insufficient oxidation potential.
Acrylate polymers are used as binders, and the molecular structures of fluorine-containing segments, cyano-linkable segments and crosslinkable segments are introduced to improve the stability, bonding strength and oxidation potential of the binder, and reduce the swelling rate and cost of the electrolyte.
Under high alkaline conditions, the degradation and cross-linking of the binder is avoided, the processing performance of the positive electrode slurry and the rate performance of the battery are improved, the oxidation potential is enhanced, and the electrolyte swelling and production costs are reduced.
Smart Images

Figure CN119899608A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery materials, and in particular to a binder and a preparation method thereof, and batteries and electrical equipment. Background Art
[0002] At present, commercial lithium-ion batteries mainly use polyvinylidene difluoride (PVDF) as the positive electrode binder of the battery, and carboxymethyl cellulose (CMC) + polymerized styrene butadiene rubber (SBR) as the negative electrode binder of the battery. As a binder for the positive electrode, it must have the following characteristics: ① It must have excellent bonding properties; ② It must be able to withstand high voltage environments; ③ It must be able to withstand organic electrolytes. PVDF occupies the position of the positive electrode binder of the battery due to its ultra-high stability, electrolyte resistance, and high oxidation potential. However, with the development of positive electrode materials in recent years, PVDF has gradually encountered bottlenecks on the technical and commercial sides. First, with the development of high-nickel ternary positive electrodes and sodium battery layered oxide positive electrode materials, the energy density of positive electrode materials has been continuously improved. Due to the high residual alkali content on the surface of the material caused by the positive electrode material precursor and the synthesis process, the positive electrode material as a whole exhibits a high alkalinity state. In the process of making positive electrode slurry, it is necessary to mix the binder and positive electrode material. A trace amount of water will cause the positive electrode slurry to form a strong alkaline environment, and the PVDF binder will cause PVDF to degrade and crosslink in a strong alkaline environment, thereby causing the slurry to gel and present a jelly phenomenon, and ultimately cannot be smoothly processed into a positive electrode sheet. In order to solve the gelation problem of PVDF, the existing alternatives include polyimide binders and polyacrylonitrile copolymer binders. Among them, polyimide, as a high-performance engineering plastic, has ultra-high stability and good tolerance to solvents, heat, voltage, etc., but it also has many problems, such as excessive swelling of the electrolyte, poor rate performance, and high cost. Polyacrylonitrile copolymers have also been widely studied as a low-cost alternative. Due to the strong interaction between the cyanide groups of the molecular chains, it can also achieve strong bonding, but the viscosity of its glue is high, which brings some difficulties to processing. In addition, the oxidation potential of polyacrylonitrile copolymers is about 4.0V, which is not suitable for battery systems such as NCM and LCO. Summary of the invention
[0003] The present application provides a binder and a preparation method thereof, as well as a battery and an electrical device, to improve the stability and processing performance of the binder in an alkaline environment, while improving the rate performance and oxidation potential of the binder and reducing the swelling rate and cost of the electrolyte.
[0004] In a first aspect, the present application provides an adhesive, which includes an acrylic polymer, wherein the number average molecular weight of the acrylic polymer is 10kDa-3000kDa, and the molecular structure of the acrylic polymer contains side chain groups, wherein the side chain groups include fluorine-containing segments, cyano segments and cross-linkable segments, wherein the mass proportion of fluorine element in the molecular structure is 3%-30%, and the mass proportion of cyano in the molecular structure is 10%-40%.
[0005] The binder of the present application is mainly composed of acrylic polymers. Among them, the fluorine-containing segment in the side chain group of the acrylic polymer introduces fluorine atoms. Since F has a high electronegativity and the CF bond energy is high, the high bond energy can give the acrylic polymer a stable skeleton structure, so that it has excellent solvent resistance and antioxidant properties. In addition, since the polarizability of the F atom is low, the prepared polymer molecule has low polarity and improved high-voltage resistance. The CF bond can also complex with Li ions to improve ionic conductivity. The cyano segment in the side chain group has an excellent intermolecular force, which gives the polymer a higher rigidity and modulus, and can also improve the viscosity of the glue and enhance the stability of the slurry. In addition, due to the introduction of the strong coordination ability cyano group, it can be complexed with the transition metal on the electrode surface, which plays a role in shielding these active ions on the positive electrode surface and reducing the decomposition of the electrode on the electrolyte. The crosslinkable segment in the side chain group can realize the formation of a chemical crosslinking network after the polymer is dried at high temperature, thereby improving its shape stability. High crosslinking degree can also reduce electrolyte swelling. By adjusting the ratio of crosslinked monomers, electrolyte swelling control can be achieved, and the balance of electronic conductivity and ionic conductivity can be achieved. Therefore, the binder of the present application can have the following advantages: 1) No degradation crosslinking reaction will occur under high alkaline conditions, which solves the problem of easy gelation of positive electrode slurry from the source; 2) Through the design of molecular segment structure, fluorine-containing segments, cyanide segments and crosslinkable segments are introduced, which can effectively improve the oxidation potential, bonding strength, electrolyte swelling and other problems, and achieve the improvement of battery performance; 3) The binder in the present application is simple to synthesize, the raw materials are not limited, and the cost is low, which can effectively solve the current high price, shortage and monopoly of PVDF materials.
[0006] In an optional implementation, the number of carbon atoms in the fluorine-containing segment is 2-8. In an optional implementation, the number of carbon atoms in the cyano segment is 2-4. In an optional implementation, the number of carbon atoms in the cross-linkable segment is 2-20. In the fluorine-containing segment, the number of carbon atoms is 2-8, which can avoid the outer layer of the polymer molecule being wrapped by the fluorine chain to reduce its adhesion. In the cyano segment, the number of carbon atoms is 2-8, which can avoid the outer layer of the polymer molecule being wrapped by the cyano chain to reduce its adhesion.
[0007] In an optional implementation, the polymerizable monomer forming the fluorinated segment is selected from a fluorinated alkenyl group or a fluorinated alkynyl group. Exemplarily, the fluorinated segment is a perfluoroalkyl group. The perfluoroalkyl group may contain multiple fluorine atoms, which may help to improve the stability of the molecular structure of the acrylic polymer.
[0008] In an optional implementation, the polymerized monomer forming the cyano segment is selected from cyano-containing alkenyl or cyano-containing alkynyl.
[0009] In an optional implementation, the polymer monomer forming the crosslinkable segment is selected from an alkenyl compound or an alkynyl compound containing a crosslinkable reaction group, wherein the crosslinkable reaction group is selected from at least one of an epoxy group, an acetoacetate group, an amide group, a carboxyl group or an N-substituted amide group. The crosslinkable segment can form a chemically crosslinked network structure after the acrylic polymer is dried at high temperature, thereby improving the shape stability of the binder. Acrylic polymers with a high degree of crosslinking can also reduce the electrolyte swelling of the binder. In addition, by adding a crosslinkable segment containing the above-mentioned groups and adjusting the proportion of crosslinkable monomers, electrolyte swelling control can be achieved, and a balance between electronic conductivity and ionic conductivity can be achieved.
[0010] In an optional implementation, the glass transition temperature of the adhesive is -20° C. to 120° C. The adhesive with this glass transition temperature can have a higher temperature processing range and reduce the ambient temperature requirement.
[0011] In a second aspect, the present application provides a method for preparing a binder, comprising:
[0012] placing a mixed monomer containing a first polymerizable monomer, a second polymerizable monomer and a third polymerizable monomer in a solvent for polymerization reaction, and obtaining an acrylic ester polymer after purification;
[0013] placing the acrylic polymer in a glue solution to form a bonding agent;
[0014] Among them, the first polymerizable monomer is a fluorine-containing acrylate monomer, and the mass proportion of the fluorine-containing acrylate monomer in the mixed monomer is 20%-80%; the second polymerizable monomer is a cyano-containing monomer, and the mass proportion of the cyano-containing monomer in the mixed monomer is 20%-80%; the third polymerizable monomer is a cross-linkable monomer that does not contain fluorine and cyano groups, and the mass proportion of the cross-linkable monomer in the mixed monomer is 1%-10%; the number average molecular weight of the acrylate polymer is 10kDa-3000kDa.
[0015] The preparation method of the present application includes an acrylic polymer formed by polymerization of a first polymerizable monomer, a second polymerizable monomer and a third polymerizable monomer. Among them, the first polymerizable monomer is a fluorine-containing acrylic monomer, and its molecule contains a fluorine-containing segment. The second polymerizable monomer contains a cyano segment. The third polymerizable monomer contains other types of polymerizable segments. Fluorine atoms are introduced into the fluorine-containing segment. Since F has a high electronegativity and the CF bond energy is high, the high bond energy can give the acrylic polymer a stable skeleton structure, so that it has excellent solvent resistance and antioxidant properties. In addition, since the polarizability of the F atom is low, the prepared polymer molecule has low polarity and improved high-voltage resistance. The CF bond can also complex with Li ions to improve ionic conductivity. The cyano segment in the side chain group has excellent intermolecular forces, which gives the polymer a higher rigidity and modulus, and can also increase the viscosity of the glue and improve the stability of the slurry. In addition, due to the introduction of the strong coordination ability cyano group, it can be complexed with the transition metal on the electrode surface, which plays a role in masking these active ions on the positive electrode surface and reducing the decomposition effect of the electrode on the electrolyte. The cross-linkable segment in the side chain group can realize the formation of a chemical cross-linked network after the polymer is dried at high temperature, thereby improving its shape stability. A high degree of cross-linking can also reduce electrolyte swelling. By adjusting the proportion of cross-linked monomers, electrolyte swelling control can be achieved, and the balance of electronic conductivity and ionic conductivity can be achieved. As a result, the binder of the present application may have the following advantages: 1) no degradation cross-linking reaction will occur under high alkaline conditions, which solves the problem of easy gelation of the positive electrode slurry from the source; 2) through the design of the molecular segment structure, fluorine-containing segments, cyano segments and cross-linkable segments are introduced, which can effectively improve the oxidation potential, bonding strength, electrolyte swelling and other problems, and realize the improvement of battery performance; 3) the binder in the present application is simple to synthesize, the raw materials are not limited, and the cost is low, which can effectively solve the current situation of high price, shortage and monopoly of PVDF materials.
[0016] In an optional implementation, the mass proportion of the fluorine-containing acrylic ester monomer in the mixed monomer is 40%-50%.
[0017] In an optional implementation, the mass proportion of the cyano group-containing monomer in the mixed monomer is 40%-50%.
[0018] In an optional implementation, the mass proportion of the third polymerizable monomer in the mixed monomer is 3%-5%.
[0019] In an optional implementation, the molecular formula of the fluorinated acrylate monomer is CH2=CRCOO(CH2): m C n F 2n+1 , wherein R is H or CH3, m≥1, n≥1, m+n≤12. m is preferably 1-2, and n is preferably 1-4.
[0020] In an optional implementation, the cyano group-containing monomer is selected from at least one of acrylonitrile, methacrylonitrile or chloroacrylonitrile. Such substances can easily undergo copolymerization reaction with vinyl groups and (meth)acrylate groups.
[0021] In an optional implementation, the third polymerizable monomer is specifically composed of a monomer containing a crosslinkable group such as a carboxyl group, a substituted acrylamide, a glycidyl ether, a multifunctional silane, and a monomer capable of copolymerizing with a vinyl group or a (meth)acrylate group. For example, the third polymerizable monomer contains at least one of an olefin group, an ether group, an amide group, and an ester group.
[0022] In an optional implementation, the third polymerizable monomer is selected from at least one of glycidyl (meth)acrylate, ethyl acetoacetate methacrylate, (meth)acrylamide, (meth)acrylic acid, N-n-butyl (iso)oxymethyl acrylamide, diacetone acrylamide or N-hydroxymethyl acrylamide.
[0023] In an optional implementation, the mixed monomer further includes an auxiliary monomer, and the auxiliary monomer is selected from at least one of alkyl (meth)acrylate, hydroxyalkyl (meth)acrylate, styrene, vinyl pyrrolidone or vinyl acetate.
[0024] In a third aspect, the present application provides a battery, comprising a positive electrode plate, wherein the positive electrode plate comprises a positive electrode active material and a binder, wherein the binder is selected from the binder of the first aspect of the present application or the binder obtained by the preparation method of the second aspect of the present application.
[0025] In a fourth aspect, the present application provides an electrical device, comprising an electrical component and the battery of the third aspect of the present application, wherein the battery provides power for the electrical device.
[0026] The technical effects that can be achieved in the third and fourth aspects mentioned above can be described with reference to the corresponding effects in the first aspect mentioned above, and will not be repeated here.
[0027] Among them, the data in the above-mentioned possible implementation methods of the present application, such as the number average molecular weight of the acrylic polymer, the number of carbon atoms in each segment, the glass transition temperature, the mass proportion of each monomer, etc., when measuring, the values within the scope of engineering measurement error should be understood to be within the range specified in the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 A schematic diagram of the working principle of the battery provided in the embodiment of the present application;
[0029] Figure 2A schematic diagram of the molecular structure of an acrylic polymer provided in an embodiment of the present application.
[0030] Reference numerals:
[0031] 11-positive electrode sheet; 12-negative electrode sheet; 13-diaphragm; 14-electrolyte; 21-fluorine-containing segment; 22-cyano segment; 23-crosslinkable segment. DETAILED DESCRIPTION
[0032] In order to make the objectives, technical solutions and advantages of the present application clearer, the present application will be further described in detail below in conjunction with the accompanying drawings.
[0033] The terms used in the following embodiments are only for the purpose of describing specific embodiments and are not intended to be limiting of the present application. As used in the specification and appended claims of the present application, the singular expressions "a", "an", "above", "the" and "this" are intended to also include expressions such as "one or more", unless there is a clear contrary indication in the context.
[0034] References to "one embodiment" or "some embodiments" etc. described in this specification mean that a particular feature, structure or characteristic described in conjunction with the embodiment is included in one or more embodiments of the present application. Thus, the phrases "in one embodiment", "in some embodiments", "in some other embodiments", "in some other embodiments", etc. that appear at different places in this specification do not necessarily refer to the same embodiment, but mean "one or more but not all embodiments", unless otherwise specifically emphasized in other ways. The terms "including", "comprising", "having" and their variations all mean "including but not limited to", unless otherwise specifically emphasized in other ways.
[0035] Figure 1 Figure 1 is a schematic diagram of the structure of a lithium-ion battery. Figure 1As shown, the lithium-ion battery may include a positive electrode sheet 11, a negative electrode sheet 12, a separator 13 and an electrolyte 14. Among them, the positive electrode sheet 11 is obtained by coating the positive electrode slurry on the positive electrode collector and drying it. The positive electrode slurry usually contains positive electrode materials and binders. Among them, the binder used in the positive electrode material of the battery needs to cope with a variety of changing scenarios, so it is required to have a variety of excellent properties. It can be summarized into three points: ① It needs to have excellent bonding properties; ② It needs to be able to withstand high voltage environments; ③ It needs to be able to withstand organic electrolytes. First of all, in order to cope with the high energy density of the battery, the current mass proportion of the binder in the positive electrode material is only 1%-2%. At such a low content, it is also necessary to ensure the bonding of the positive electrode powder and the stability of the electrode sheet processing, which requires the positive electrode binder to have excellent bonding ability. On the one hand, it requires a strong interaction between the polymer and the powder, and on the other hand, the polymer itself needs to have a high mechanical strength. Secondly, during the charging process, the voltage on the positive electrode side will reach above 4.0V, and for LCO materials, it will even reach above 4.5V, which requires the binder to have a high oxidation potential so that it will not decompose during the battery cycle and keep the battery stable. Finally, the battery is soaked with a large amount of organic electrolyte. As an organic polymer, the binder is easily soluble in organic liquids, but the binder needs to be able to remain stable in the electrolyte system without dissolving, and the swelling degree needs to be controlled below 50%.
[0036] An embodiment of the present application provides a binder including an acrylic polymer. Figure 2 A schematic diagram of the molecular structure of an acrylic polymer provided in an embodiment of the present application. The number average molecular weight of the acrylic polymer in the adhesive in the embodiment of the present application is 10 kDa-3000 kDa, and the molecular structure of the acrylic polymer contains side chain groups, and the side chain groups include fluorine-containing segments 21, cyano segments 22 and cross-linkable segments 23, wherein the mass proportion of fluorine in the molecular structure is 3%-30%, and the mass proportion of cyano in the molecular structure is 10%-40%.
[0037] The binder of the embodiment of the present application, wherein the acrylic polymer does not undergo degradation and cross-linking reaction under alkaline conditions, solves the problem of easy gelation of the slurry under highly alkaline conditions from the source, and facilitates the processing and manufacturing of the positive electrode slurry.
[0038] Among them, the molecular structure of the acrylic polymer contains side chain groups. The number of carbon atoms in the fluorine-containing segment in the side chain group is 2-8. The polymerized monomer forming the fluorine-containing segment can be selected from a fluorine-containing alkenyl or a fluorine-containing alkynyl. The fluorine-containing segment in the side chain group has a high electronegativity of F and a high CF bond energy. The high bond energy can give the acrylic polymer a stable skeleton structure, so that it has excellent solvent resistance and antioxidant properties. Since the polarizability of the F atom is low, the prepared polymer molecule has low polarity and improved high voltage resistance. The CF bond can also complex with Li ions to improve ionic conductivity. The fluorine-containing segment is a polyfluoroalkyl group or a perfluoroalkyl group. The increase in the number of fluorine atoms can help to further improve the stability of the skeleton structure.
[0039] The side chain group contains a cyano segment. The number of carbon atoms in the cyano segment is 2-4. The polymerized monomer that forms the cyano segment is selected from a cyano-containing alkenyl group or a cyano-containing alkynyl group. The cyano segment in the side chain group has an excellent intermolecular force, which gives the polymer higher rigidity and modulus, and can also increase the viscosity of the glue and improve the stability of the slurry. In addition, due to the introduction of the cyano group with strong coordination ability, it can complex with the transition metal on the electrode surface, shielding these active ions on the positive electrode surface and reducing the decomposition effect of the electrode on the electrolyte.
[0040] The side chain group contains a crosslinkable segment. The number of carbon atoms of the crosslinkable segment is 2-20. The polymerizable monomers forming the crosslinkable segment are selected from alkenyl compounds or alkynyl compounds containing crosslinkable reaction groups, wherein the crosslinking reaction groups are selected from epoxy groups, acetoacetoxy groups, amide groups, carboxyl groups, and N-substituted amide groups. The crosslinkable segments in the side chain groups can realize the formation of a chemical crosslinking network after the polymer is dried at high temperature, thereby improving its shape stability. A high degree of crosslinking can also reduce electrolyte swelling. By adjusting the proportion of crosslinking monomers, electrolyte swelling control can be achieved, and a balance between electronic conductivity and ionic conductivity can be achieved.
[0041] In the embodiment of the present application, the glass transition temperature of the adhesive is -20°C to 120°C, preferably 80°C to 100°C. The glass transition temperature can facilitate the expansion of the application scenarios of the adhesive. Among them, the number average molecular weight of the acrylic polymer in the embodiment of the present application can be 400-600kDa.
[0042] It can be understood that the adhesive of the embodiment of the present application, in addition to containing acrylic polymers, may also contain other additives, such as conductive additives (conductive carbon black, carbon nanotubes, graphene), dispersing additives (dispersants, surfactants), rheological additives, film-forming additives, etc.
[0043] The above is an explanation of the specific molecular structure and composition of the binder of the present application. The following is an explanation of the specific preparation method of the binder. The preparation process of the binder of the embodiment of the present application can be synthesized by emulsion polymerization or suspension polymerization, or by intermittent, semi-continuous, or continuous synthesis process.
[0044] The binder of the embodiment of the present application may be a multi-polymer, for example, it may be composed of n monomers (2≤n≤10), and the copolymer structure may be a random, block, alternating, grafted, etc. The polymerization form between the monomers is not specifically limited.
[0045] The method for preparing the binder of the embodiment of the present application comprises the following steps:
[0046] S1. Place a mixed monomer containing a first polymerizable monomer, a second polymerizable monomer and a third polymerizable monomer in a solvent for polymerization reaction, and obtain an acrylic acid ester polymer after purification. The number average molecular weight of the acrylic acid ester polymer is 10 kDa-3000 kDa.
[0047] S2. placing the acrylic polymer in a solvent to form a binder.
[0048] Wherein, the first polymerizable monomer is a fluorinated acrylate monomer, and the mass proportion of the fluorinated acrylate monomer in the mixed monomer is 20%-80%, preferably 40%-50%. The molecular formula of the fluorinated acrylate monomer is CH2=CRCOO(CH2) m C n F 2n+1 , wherein R is H or CH3, m≥1, n≥1, m+n≤12. m is preferably 1-2, and n is preferably 1-4.
[0049] The second polymerizable monomer is a cyano-containing monomer, and the mass proportion of the cyano-containing monomer in the mixed monomer is 20%-80%, preferably 40%-50%. The cyano-containing monomer is selected from at least one of acrylonitrile, methacrylonitrile or chloroacrylonitrile. Such substances can easily copolymerize with vinyl and (meth)acrylate groups.
[0050] The third polymerizable monomer is a crosslinkable monomer that does not contain fluorine and cyano groups, and the mass proportion of the crosslinkable monomer in the mixed monomer is 1%-10%, preferably 3%-5%. The specific composition of the third polymerizable monomer is a monomer containing crosslinkable groups such as carboxyl, substituted acrylamide, glycidyl ether, multifunctional silane, and a monomer that can copolymerize with vinyl and (meth)acrylate groups. For example, the third polymerizable monomer contains at least one of alkenyl, ether, amide, and ester groups. Exemplarily, the third polymerizable monomer is selected from at least one of (meth) acrylic acid glycidyl ether, acetoacetoxyethyl methacrylate, (meth) acrylamide, (meth) acrylic acid, N-n-butyl (iso)oxymethyl acrylamide, diacetone acrylamide, or N-hydroxymethyl acrylamide.
[0051] The mixed monomer further comprises an auxiliary monomer, and the auxiliary monomer is selected from at least one of alkyl (meth)acrylate, hydroxyalkyl (meth)acrylate, styrene, vinyl pyrrolidone or vinyl acetate.
[0052] In one embodiment, the preparation method of the adhesive of the present application comprises the following steps:
[0053] S11, preparing monomer pre-emulsion: dispersing the first polymerizable monomer, the second polymerizable monomer, the third polymerizable monomer, the emulsifier and auxiliary components (buffer, masking agent, stabilizer) into a solvent such as water according to the designed proportion, and emulsifying them uniformly by high-speed shear stirring to form a stable pre-emulsion.
[0054] S12, emulsion polymerization: add 20%-30% pre-emulsion to the reactor, add 20% initiator to initiate polymerization until the reaction solution shows blue light, gradually drip the pre-emulsion and initiator solution into the reactor. Maintain the temperature to react until all the pre-emulsion is dripped, and continue to keep the temperature for a while. Inert gas protection is required throughout the process.
[0055] S13, polymer separation: add demulsifier to the emulsion after the reaction is completed, separate the solid and liquid to obtain polymer solid powder particles, wash with deionized water to remove the remaining emulsifier, demulsifier and inorganic salt, dry and crush to obtain the final product.
[0056] The adhesive of the present application will be described in detail below with reference to specific embodiments and comparative examples.
[0057] Example 1
[0058] This embodiment is a binder, which is prepared by the following method.
[0059] Measure by weight, add 7.5 parts of CO-436 emulsifier to 350 parts of water, stir and dissolve. Add 70 parts of acrylonitrile, 70 parts of trifluoroethyl methacrylate, 5 parts of acrylic acid glycidyl ether and 1 part of acrylic acid monomer, stir at 350rpm for 30min for pre-emulsification, control the temperature at 10°C, and pass nitrogen protection. Take out 80% of the pre-emulsion in the reaction bottle, add 0.2 initiator ammonium persulfate to the remaining pre-emulsion, heat to 70°C, and react for 1 hour until blue light appears. Keep the temperature at 70°C, slowly add the initiator solution and pre-emulsion, and add them in 3 hours. Heat to 75°C and keep warm for 1h. After cooling, add 100 parts of 5% NaCl solution, stir to break the emulsion, separate, and wash the solid binder powder with pure water 3 times until there is no obvious foam. The binder material can be obtained after drying.
[0060] The above-mentioned adhesive material was dissolved into a 5% solid content glue solution using N-methylpyrrolidone (NMP) to obtain an adhesive.
[0061] Example 2
[0062] This embodiment is a binder. The difference between this embodiment and embodiment 1 is that 70 parts of methacrylonitrile are used instead of acrylonitrile, and 70 parts of perfluorobutyl ethyl methacrylate are used instead of trifluoroethyl methacrylate. Other than that, the polymerization process is the same as that of embodiment 1.
[0063] Example 3
[0064] This embodiment is a binder. The difference between this embodiment and embodiment 1 is that 70 parts of methacrylonitrile are used instead of acrylonitrile, and 5 parts of N-hydroxymethyl acrylamide are used instead of glycidyl acrylate. Other than that, the polymerization process is the same as that of embodiment 1.
[0065] Example 4
[0066] This embodiment is a binder. The difference between this embodiment and embodiment 1 is that 50 parts of acrylonitrile and 90 parts of trifluoroethyl methacrylate are used. Other than that, the polymerization process is the same as that of embodiment 1.
[0067] Example 5
[0068] This embodiment is a binder. The difference between this embodiment and embodiment 1 is that 70 parts of perfluorohexylethyl acrylate is used instead of trifluoroethyl methacrylate. Other than that, the polymerization process is the same as that of embodiment 1.
[0069] Example 6
[0070] This embodiment is a binder. The difference between this embodiment and embodiment 1 is that 3 parts of acrylic acid glycidyl ether and 3 parts of acrylic acid monomer are used. Other than that, the polymerization process is the same as that of embodiment 1.
[0071] Comparative Example 1
[0072] Comparative Example 1 directly uses commercial lithium-grade PVDF binder material, which is dissolved in N-methylpyrrolidone (NMP) to form a 5% solid content glue solution for use.
[0073] Comparative Example 2
[0074] This comparative example is a binder, which differs from Example 1 in that 70 parts of ethyl methacrylate are used to replace trifluoroethyl methacrylate. Other than that, the polymerization process is the same as that of Example 1.
[0075] Comparative Example 3
[0076] This comparative example is a binder, which differs from Example 1 in that 70 parts of trifluoroethyl methacrylate are used to replace acrylonitrile. That is, this comparative example does not contain acrylonitrile, and the amount of trifluoroethyl methacrylate is 140 parts. Other than that, the polymerization process is the same as that of Example 1.
[0077] Comparative Example 4
[0078] This comparative example is a binder, which differs from Example 1 in that acrylic acid glycidyl ether and acrylic acid monomer are removed from Example 1. Other than that, the polymerization process is the same as that of Example 1.
[0079] The positive electrode slurry was prepared using the binders of Examples 1-6 and Comparative Examples 1-4, and the battery was assembled. The preparation process of the positive electrode slurry and the battery is as follows.
[0080] Positive electrode slurry stirring: 40 parts of binder (5wt%), 2 parts of superconductive carbon black and 96 parts of ternary positive electrode powder with an average particle size of 8μm were added with 10 parts of NMP as a solution and mixed with a planetary mixer to prepare a battery positive electrode slurry.
[0081] Preparation of battery pole piece: The positive electrode slurry prepared above was evenly coated on a 10 μm aluminum foil using an extrusion coater and dried at 100°C. Then, it was rolled using a biaxial roller press to obtain a 150 μm double-layer coated pole piece.
[0082] Battery production: The obtained battery pole pieces are die-cut into strips, matched with double-sided coated graphite negative electrodes with corresponding coating loads, assembled to form laminated soft-pack batteries, added with electrolyte, and after chemical composition, a 4000mAh soft-pack battery cell is prepared for performance testing.
[0083] Battery test: The data during battery processing and the battery performance test data are listed in Table 1.
[0084] Test items and test methods
[0085] Viscosity: The viscosity of the adhesive was tested using a rotational viscometer at room temperature (25±5°C) (standard method GB / T 2794).
[0086] Swelling degree: Take the dry adhesive film of the adhesive and weigh it to get the mass m1. Soak it in the electrolyte of the lithium battery and leave it at room temperature for 48 hours. After taking it out, wipe off the excess electrolyte on its surface and weigh it to get the mass m2. Swelling degree = (m2-m1) / m1%.
[0087] Electrochemical window: Place the adhesive dry film between two layers of lithium sheets to assemble a button-type battery. Use an electrochemical workstation to perform a linear voltammetric scan and record the voltage value when the current rises.
[0088] Peel strength: The binder, cathode powder and conductive carbon were mixed and dissolved in NMP solvent in a mass ratio of 1.5%:97%:1.5%, and a slurry with a solid content of 60% was prepared by high-speed dispersion and stirring, and then coated on aluminum foil. After drying, the electrode was taken and its 180° peel strength was tested using double-sided tape.
[0089] Gel time: The positive electrode slurry obtained by stirring as described above was placed in an environment with a humidity of 40%, and its fluidity change was observed. The time when the slurry could not flow was recorded as its gel time.
[0090] Battery performance test: The binder prepared above was used in the production of ternary battery cells to prepare soft-pack battery cells with a capacity of 3000mAh. The battery performance was tested to obtain its weight energy density, first efficiency, 1C-stage charge cycle, and 60°C storage for 28 days performance data.
[0091] Table 1
[0092]
[0093] Table 1 (continued)
[0094]
[0095]
[0096] It can be seen from the data in Table 1 that the electrochemical window, weight energy density and cycle performance of the batteries prepared using the binder of Examples 1-6 of the present application are not much different from those of the PVDF binder of Comparative Example 1. However, the bonding time of the binder of the examples of the present application is much longer than that of the PVDF of Comparative Example 1, indicating that replacing the traditional PVDF binder with the binder of the present application can avoid the problem of gelation in the process of preparing the positive electrode slurry while enabling the battery to obtain the same electrical performance.
[0097] It can be seen from the relevant test data of Example 1 and Comparative Example 2 that when the molecular structure of the acrylic ester polymer does not contain a fluorine-containing segment, its electrochemical window is reduced, indicating that the pressure resistance and oxidation resistance of the sample in Comparative Example 2 will be significantly reduced. This shows that when the molecular structure of the acrylic ester polymer contains a fluorine-containing segment, the electrochemical window of the obtained polymer is wider, it can remain stable even at high voltage, and has good oxidation resistance and swelling resistance, and has excellent performance after being applied to secondary batteries.
[0098] It can be seen from the relevant test data of Example 1 and Comparative Example 3 that when the molecular structure of the acrylic polymer does not contain a cyano segment, its cycle performance is reduced, indicating that the strength, structural stability and electrolyte friendliness of the sample of Comparative Example 3 are reduced. This shows that the introduction of the cyano segment can, on the one hand, achieve an increase in the viscosity of the binder slurry, and on the other hand, through the cyano group, the polymer can coordinate with the transition metal ions in the positive electrode material, reduce the catalytic decomposition of the electrolyte, and improve the cycle stability.
[0099] It can be seen from the relevant test data of Example 1 and Comparative Example 4 that when the molecular structure of the acrylic polymer does not contain a crosslinkable segment, its molecular weight and adhesive force performance will be significantly reduced, and the electrolyte swelling degree will be significantly increased. This shows that the introduction of the crosslinkable segment can effectively reduce the swelling of the electrolyte, and by adjusting the proportion of the crosslinking monomer, the swelling of the electrolyte can be controlled and the balance of electronic conductivity and ionic conductivity can be achieved.
[0100] In summary, the binder of the embodiment of the present application is easy to synthesize, has no restrictions on raw materials, and is low in cost. The binder of the embodiment of the present application can withstand alkaline environments and will not cause gelation problems in the positive electrode slurry. The positive electrode slurry of the sodium-based high-alkali system has normal fluidity for more than 2 weeks, and is a key material for the practical application of high-alkaline materials such as sodium-based positive electrodes, high-nickel ternary positive electrodes, and lithium supplements.
[0101] The above are only specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A binder, characterized in that: The binder includes an acrylic polymer, the number average molecular weight of the acrylic polymer is 10kDa-3000kDa, the molecular structure of the acrylic polymer contains side chain groups, the side chain groups include fluorine-containing segments, cyano segments and cross-linkable segments, wherein the mass proportion of fluorine element in the molecular structure is 3%-30%, and the mass proportion of cyano in the molecular structure is 10%-40%.
2. The adhesive according to claim 1, characterized in that The number of carbon atoms in the fluorine-containing segment is 2-8, the number of carbon atoms in the cyano segment is 2-4, and the number of carbon atoms in the cross-linkable segment is 2-20.
3. The adhesive according to claim 1 or 2, characterized in that: The polymerizable monomers forming the fluorine-containing chain segment are selected from fluorine-containing alkenyl compounds or fluorine-containing alkynyl compounds.
4. The adhesive according to claim 3, characterized in that The fluorine-containing segment is a perfluoroalkyl group.
5. The adhesive according to any one of claims 1 to 4, characterized in that: The polymerized monomer forming the cyano segment is selected from cyano-containing alkenyl compounds or cyano-containing alkynyl compounds.
6. The adhesive according to any one of claims 1 to 5, characterized in that: The polymerizable monomers forming the crosslinkable chain segments are selected from alkenyl compounds or alkynyl compounds containing crosslinkable reaction groups, wherein the crosslinking reaction groups are selected from epoxy groups, acetoacetoxy groups, amide groups, carboxyl groups, and N-substituted amide groups.
7. The adhesive according to any one of claims 1 to 6, characterized in that: The binder has a glass transition temperature of -20°C to 120°C.
8. A method for preparing a binder, characterized in that: include: placing a mixed monomer containing a first polymerizable monomer, a second polymerizable monomer and a third polymerizable monomer in a solvent for polymerization reaction, and obtaining an acrylic ester polymer after purification; placing the acrylic polymer in a solvent to form a binder; Among them, the first polymerizable monomer is a fluorine-containing acrylate monomer, and the mass proportion of the fluorine-containing acrylate monomer in the mixed monomer is 20%-80%; the second polymerizable monomer is a cyano-containing monomer, and the mass proportion of the cyano-containing monomer in the mixed monomer is 20%-80%; the third polymerizable monomer is a cross-linkable monomer that does not contain fluorine and cyano groups, and the mass proportion of the cross-linkable monomer in the mixed monomer is 1%-10%; the number average molecular weight of the acrylate polymer is 10kDa-3000kDa.
9. The preparation method according to claim 8, characterized in that: The molecular formula of the fluorinated acrylic ester monomer is CH2=CRCOO(CH2) m C n F 2n+1 , wherein R is H or CH3, m≥1, n≥1, m+n≤12.
10. The preparation method according to claim 8 or 9, characterized in that: The cyano group-containing monomer is selected from at least one of acrylonitrile, methacrylonitrile or chloroacrylonitrile.
11. The preparation method according to any one of claims 8 to 10, characterized in that: The third polymerizable monomer is selected from at least one of glycidyl (meth)acrylate, ethyl acetoacetate methacrylate, (meth)acrylamide, (meth)acrylic acid, N-n-butyl (iso)oxymethyl acrylamide, diacetone acrylamide or N-hydroxymethyl acrylamide.
12. The preparation method according to any one of claims 8 to 11, characterized in that: The mixed monomer further includes an auxiliary monomer, and the auxiliary monomer is selected from at least one of alkyl (meth)acrylate, hydroxyalkyl (meth)acrylate, styrene, vinyl pyrrolidone or vinyl acetate.
13. A battery, characterized in that: The invention comprises a positive electrode plate, wherein the positive electrode plate comprises a positive electrode active material and a binder, wherein the binder is selected from the binder as described in any one of claims 1 to 7 or the binder obtained by the preparation method as described in any one of claims 8 to 12.
14. An electrical device, characterized in that: It comprises an electrical component and the battery as claimed in claim 13, wherein the battery provides power for the electrical device.
Citation Information
Cited By
Binder and preparation method therefor, battery and electric device
EP4782513A1